SERBIAN BLACK TRUFFLE TUBER AESTIVUM: MICROBIOTA AND EFFECT OF DIFFERENT FREEZING REGIMES ON VOLATILE AROMA COMPOUNDS DURING STORAGE - Paunovic, Dusanka; Mirković, Milica; Mirkovic, Nemanja; Tesevic, Vele; Stankovic Jeremic, Jovana; Todosijevic, Marina; Radulovic, Zorica (Journal of Agricultural Sciences (Belgrade), 2023)
The use of truffles in food is based mainly on artificial flavors addition, aiming to achieve an intense aroma in the products. As truffle is a natural product with nutritional and functional properties, it is important to find optimal way for truffle storage. As the microbiota contribute to truffles aroma, the bacterial and yeast composition in rhizosphere and fruiting body of the Serbian truffle, as well as the impact of at different freezing methods on volatile profile of the truffle Tuber aestivum during 90 days of the storage were determined. Bacterial and yeast isolation from fresh truffle was conducted and isolates were identified using 16s rRNA and 18s rRNA. Effect of truffles freezing at -20°C, -80°C with and without previous dipping in liquid N2 on the volatile compounds was observed using GC/MS. Results demonstrated that isolated bacteria belonged to the phylum Proteobacteria, Firmicutes and Actinobacteria, where identified species mainly belonged to Firmicutes, genus Bacillus sp. Isolated yeasts were identified as Cryptococcus sp., Debaromyces hanseinii, Candida fermentati and Rhodotorula mucilaginosa. The GC/MS analysis revealed differences in volatile profile of fresh and frozen truffles. Frozen samples were richer with compounds 2-butanone, 2-methyl-butanal, methanethiol and 2 butanol after freezing or during storage. Content of DMS, acetaldehyde, 3-octanone, ethanol, 2-methyl-1-propanol significantly decrease immediately after freezing. Overall, gained results indicated that freezing of truffles as preservation method had profound effect on volatile compounds, where previous dipping in liquid N2 showed no significant impact on volatile profile of truffle Tuber aestivum.